2013
DOI: 10.1002/jctb.4119
|View full text |Cite
|
Sign up to set email alerts
|

Continuous sodium hydroxide‐catalyzed pretreatment of empty fruit bunches (EFB) by continuous twin‐screw‐driven reactor (CTSR)

Abstract: BACKGROUND: Since extrusion has many desirable characteristics such as high shear, rapid mixing, short residence time, controllable barrel temperature, and adaptability to process modification, the technology has been applied as a viable continuous pretreatment method for empty fruit bunches (EFB). RESULTS:Optimized conditions for a continuous twin-screw-driven reactor (CTSR) were determined to be 170 • C barrel temperature, 1.6% (w/v) sodium hydroxide, 1:8 solid to liquid ratio, and 5 rpm screw rotational spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Extrusion alone is a mechanical process that provides high shear, fast heat transfer and thorough mixing [20] and the possibility to combine it with other pretreatments adds interest to the process application [21,22]. Chemical reagents and biocatalysts can also be added during extrusion [17,[23][24][25], resulting in a mixture of physical, thermal, chemical and/or biological effects that enhance the disruption of the lignocellulosic matrix. Among the different process possibilities, extrusion combined with an alkaline chemical agent (most notably NaOH) has been proven to be successful operating at moderate temperatures and pressures and causing no or very low sugar degradation compared to other chemical pretreatments [19,26].…”
Section: Introductionmentioning
confidence: 99%
“…Extrusion alone is a mechanical process that provides high shear, fast heat transfer and thorough mixing [20] and the possibility to combine it with other pretreatments adds interest to the process application [21,22]. Chemical reagents and biocatalysts can also be added during extrusion [17,[23][24][25], resulting in a mixture of physical, thermal, chemical and/or biological effects that enhance the disruption of the lignocellulosic matrix. Among the different process possibilities, extrusion combined with an alkaline chemical agent (most notably NaOH) has been proven to be successful operating at moderate temperatures and pressures and causing no or very low sugar degradation compared to other chemical pretreatments [19,26].…”
Section: Introductionmentioning
confidence: 99%
“…The amount of sugars recovered in the filtrate is in any case the same. Supporting these findings, Choi et al [33] found that the glucan content in the extrudate increased and the lignin content decreased as the L/S ratio increased from 4 to 8 for the alkaline pretreatment of empty fruit bunches, especially at high NaOH loadings (>5% NaOH/DM).…”
Section: Effect Of L/s Ratio In the Reaction Zonementioning
confidence: 80%
“…Other authors have reported deacetylation and/or delignification in alkaline extrusion of different biomasses. For example, Choi et al [33] extruded empty fruit bunches at high temperature (170 • C) and low screw speed (5 rpm) and found that, as the amount of catalyst increased from 5% to 20% NaOH/DM, the glucan content in the extrudate increases, corresponding to a decrease of the hemicellulosic sugars and lignin due to solubilization. Similar behavior was reported by Han et al [35] and Duque et al [27] on alkali-extruded barley straw.…”
Section: Effect Of Naoh/dm Ratiomentioning
confidence: 99%
“…Screw speeds less than 100 rpm are considered low and those above 120 rpm are considered high. In particular cases, it can be set very low (down to 5 rpm), or very high (up to 420 rpm) [59,68,115,116]. As noted in the preview sections, screw speed influences the torque, the SME, the barrel temperature, the residence time, and the substrate flow rate.…”
Section: Screw Speedmentioning
confidence: 99%